2018
DOI: 10.2172/1467472
|View full text |Cite
|
Sign up to set email alerts
|

Initial Evaluation of CaSDB MOF Xe and Kr Capacities

Abstract: NTRD-MRWFD-2018-000194 INL/EXT-18-44890 DISCLAIMER This information was prepared as an account of work sponsored by an agency of the U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The BET analysis concluded that the material had a surface area of 219 m 2 /g. For comparison, BET analyses on previous batches of the compressed CaSDB yielded surface areas of 4 m 2 /g and 81 m 2 /g (Welty, Garn, & Greenhalgh, 2018).…”
Section: Casdbmentioning
confidence: 99%
See 1 more Smart Citation
“…The BET analysis concluded that the material had a surface area of 219 m 2 /g. For comparison, BET analyses on previous batches of the compressed CaSDB yielded surface areas of 4 m 2 /g and 81 m 2 /g (Welty, Garn, & Greenhalgh, 2018).…”
Section: Casdbmentioning
confidence: 99%
“…The resultant material was tested at INL. Initial testing concluded that CaSDB had a sufficient saturation capacity for Xe, but a low breakthrough capacity (Welty, Garn, & Greenhalgh, 2018). The physical examination of the material in the 2016 report refers to CaSDB as being easily friable to a fine dust, which will pose engineering challenges when designed for use in a flow through process.…”
Section: Introductionmentioning
confidence: 99%